Phytoplankton and Bacterial Responses to Monsoon-Driven Water Masses Mixing in the Kuroshio Off the East Coast of Taiwan - Lai, Chao-Chen; Wu, Chau-Ron; Chuang, Chia-Ying; Tai, Jen-Hua; Lee, Kuo-Yuan; Kuo, Hsiang-Yi; Shiah, Fuh-Kwo (Frontiers in Marine Science, 2021)
This study demonstrated that in summer, the mixing of the South China Sea (i.e. SCS) and the Kuroshio current (i.e. KC) waters enhanced biological biomasses/activities in the cape of southern Taiwan. Based on backward-trajectory analyses conducted by an observation-validated 3-D model, we identified that the prevailing southwest monsoon drove a northeastward “intrusion” of the SCS waters, and resulted in mixing with KC. Biogeochemical responses to the mixing were examined in a cruise survey with 8 stations across the KC at the east coast of southern Taiwan. Two stations were chosen for the anchored study. The temperature-salinity diagrams ascertained that the experiment site (i.e. ESite) was affected by the SCS-KC mixing, and the control site (i.e. CSite) was purely KC water. In the euphotic zone (~100m depth), the averaged values of nitrate (1.62±0.89 M), chlorophyll-a (Chl-a, 0.36±0.14mg m-3) and, primary production (PP; 3.46±1.37mgC m-3 d-1) of the ESite were 54X, 2.6X and 3.8X higher than those of the CSite (nitrate, 0.03±0.03M; Chl-a, 0.14±0.04 mg m-3 and, PP, 0.91±0.47 mgC m-3 d-1) respectively. The maximal bacterial production (BP) at the ESite (3.31 mgC m-3 d-1) was 82% higher in comparison with that of the CSite (1.82 mgC m-3 d-1). The readings of Chl-a showed no trend with BP in the oligotrophic CSite, but positive relationship was found among these measurements at the mesotrophic ESite. We suggested that the oligotrophic environment at the CSite tended to bring about a longer/more complex food-web that was more efficient at recycling, bacteria might receive many other substrate sources apart from phytoplankton. Moreover, bacteria-algae competition for inorganic minerals could be more severe in oligotrophic water, resulting in a situation that bacterial behavior tended to deviate from that of phytoplankton.